TAJDID PENDIDIKAN BADIUZZAMAN SAID NURSI DALAM KITAB RASAIL AN-NUR (Education’s Reform of Badiuzzaman Said Nursi in the Rasail An-Nur) - Mohd Noor, Muaz; Abd. Latif, Faizuri (Journal of Al-Tamaddun, 2012)
The condition of Muslims around the 20th century AD was pathetic. Challenges faced by humanity at that time was way-out. Their belief and faith were being attacked from all angles. Fallacious and superstitious ideologies in the form of -isms such as secularism began to attack the Muslim minds. As a result the Muslims and Muslim countries became more backward and undeveloped. Chaos took place as non-Muslim leaders from the West began to interfere with the Islamic countries. Then a British politician who is anti-Islamic Turkish made a statement , "We cannot control the Muslims as long as we do not separate their book of Quran from them". Strings of events from this revolting remark made Badiuzzaman Said Nursi (1876-1960) vowed he would prove that the Quran is a spiritual sun and cannot be destroyed altogether. He is determined to restore the once glorious civilization and Islamic sciences as during the previous Islamic caliphates. By doing analysis and research on several parts from the 14 main volumes of Rasail an-Nur, the author is able to explain and clarify the characteristics, methods as well as approaches of educational reformers confronted by Badiuzzaman Said Nursi, whereby from his aim is to create university system, the creation of madrasahs and small institutions that unite islamic religious knowledge and science.